Crystal structure and interactions of the Tof1–Csm3 (Timeless–Tipin) fork protection complex - Grabarczyk, Daniel B (Nucleic Acids Res, 2020)
The Tof1–Csm3 fork protection complex has a central role in the replisome—it promotes the progression of DNA replication forks and protects them when they stall, while also enabling cohesion establishment and checkpoint responses. Here, I present the crystal structure of the Tof1–Csm3 complex from Chaetomium thermophilum at 3.1 Å resolution. The structure reveals that both proteins together form an extended alpha helical repeat structure, which suggests a mechanical or scaffolding role for the complex. Expanding on this idea, I characterize a DNA interacting region and a cancer-associated Mrc1 binding site. This study provides the molecular basis for understanding the functions of the Tof1–Csm3 complex, its human orthologue the Timeless–Tipin complex and additionally the Drosophila circadian rhythm protein Timeless.